Rancang Bangun Website Penjualan Frozen Food Berbasis Framework CodeIgniter - Chandra, Conchita Junita (STIKOM Uyelindo Kupang, 2022)
The COVID-19 pandemic requires the government to impose large-scale social restrictions in the territory of Indonesia, which has an impact on various areas of life including trade, where there has been a significant decline in sales figures in retail stores. COVID-19 also causes fear to do activities outside the house, including buying groceries every day. On the other hand, online sales have increased. By seeing the increase in the use of technology during the pandemic, selling frozen food through the website is an alternative, where ready-to-cook food can be easily and safely obtained by consumers. This website can also help frozen food business owners to manage product data and transaction data for producing monthly sales reports quickly and efficiently, as well as a promotional tool with the Customer Relationship Management feature. This website mas made with the Modified Waterfall development model, and was built with the CodeIgniter framework to handle application workflows and Boostraps to handle the appearance of the website.